THE EFFECT OF PH AND IONIC STRENGTH ON PROTON ADSORPTION BY THE THERMOPHILIC BACTERIUM ANOXYBACILLUS FLAVITHERMUS - Burnett P.G.; Heinrich H.; Peak D.; Bremer P.J.; McQuillan A.J.; Daughney C.J. (My University, 2006)
Numerous studies have utilized surface complexation theory to model proton adsorption behaviour onto mesophilic bacteria. However, few experiments, to date, have investigated the effects of pH and ionic strength on proton interactions with thermophilic bacteria. In this study, we characterize proton adsorption by the thermophile Anoxybacillus flavithermus by performing acid-base titrations and electrophoretic mobility measurements in NaNO3 (0.001-0.1 M). Equilibrium thermodynamics (Donnan model) were applied to describe the specific chemical reactions that occur at the water-bacteria interface. Acid-base titrations were used to determine deprotonation constants and site concentrations for the important cell wall functional groups, while electrophoretic mobility data were used to further constrain the model. We observe that with increasing pH and ionic strength, the buffering capacity increases and the electrophoretic mobility decreases. We develop a single surface complexation model to describe proton interactions with the cells, both as a function of pH and ionic strength. Based on the model, the acid-base properties of the cell wall of A. flavithermus can best be characterized by invoking three distinct types of cell wall functional groups, with pKa values of 4.94, 6.85, and 7.85, and site concentrations of 5.33, 1.79, and 1.42 ? 10-4 moles per gram of dry bacteria, respectively. A. flavithermus imparts less buffering capacity than pure mesophilic bacteria studied to date because the thermophile possesses a lower total site density (8.54 ? 10-4 moles per dry gram bacteria). ? 2006 Elsevier Inc. All rights reserved.
Keywords: ADSORPTION; ELECTROKINESIS; IONIC COMPOSITION; PH; THERMOPHILIC BACTERIUM; ANOXYBACILLUS FLAVITHERMUS; BACTERIA (MICROORGANISMS)